Mariia Dmytrivna Kultaieva – a bright personification of philosophical and pedagogical creativity - Bakirov, Vil (Filosofiya osvity. Philosophy of Education, 2024)
Words of gratitude and deep respect for Mariia Dmitrivna Kultaieva from her colleague and friend Vil Savbanovych Bakirov.